Driving factors for decoupling water resources ecological footprint and economic growth in water-deficient cities dominated by agriculture - Wenqi Zhang; Defu Liu; Xianming Chen; Xiaoguo Zhou; Yifan Ding; Jialei Zhang (Water Science and Technology, 2023)
To explore the key factors and specific thresholds of water resources limiting economic development, and to provide technical support for water resources management in cities dominated by agriculture similar to Zhangjiakou. We used the Tapio elastic decoupling method to quantitatively evaluate the decoupling relationship between the water resources ecological footprint (WEF) and economic growth. Then the logarithmic mean Divisia index (LMDI) and mathematical statistics are used to identify the key factors and threshold effects. The results show a significant decreasing trend in the WEF and obvious spatial differences in Zhangjiakou between 2006 and 2015, with agricultural ecological footprint dominating all districts and counties (77.54 ± 14.35%). The changes in technological effect are a contributing factor to the decoupling between the WEF and the economy in Zhangjiakou, while the economic effect is the main restricting factor. In particular, there is a high correlation between the WEF and the number of water-saving irrigation machines and the total power of agricultural machinery. According to the findings, for water-scarce cities such as Zhangjiakou, where agriculture is the primary focus, it is suggested that increasing the number of agricultural machinery can effectively alleviate the problem of water scarcity constraining economic development. HIGHLIGHTS Combining the water resources ecological footprint theory with the Tapio decoupling model, this paper analyses the changes of water resources ecological footprint and decoupling state in different districts and counties of Zhangjiakou City in terms of time and space.; Combining LMDI modelling with mathematical and statistical methods to analyse the key factors affecting water resources and economic change in Zhangjiakou.;